Spectrum of Haemoglobinopathies in Population of Lahore District - Rahim, Arrosa; Munir, Asma; Bashir, Faiza; Zafar, Faryal; Zahid, Rabia; Haseeb, Hafiz Muhammad (Journal of Fatima Jinnah Medical University, 2024)
Background: Haemoglobinopathies describe a group of genetic disorders in which one or more globin chains are abnormally developed. Thalassemias are a common cause of hypochromic microcytic anemia, which arises from the reduced or absent synthesis of the globin chain of haemoglobin. Studies from various regions of Pakistan have indicated variable prevalence of the disease in Pakistani population with significant ethnic and geographical variations. This study was conducted to find the range of haemoglobinopathies among the population of Lahore District. Patients and Methods: It was a descriptive cross-sectional study conducted at Haematology, Pathology Department, SIMS/Services Hospital, Lahore from 18-3-2021 to 18-9-2021. 364 Patients with both genders and age 1-65 years presenting with anaemia were enrolled in this study. A 5ml sample of intravenous blood was drawn and placed in an EDTA anticoagulant container. The data was analyzed using Statistical Package for Social Sciences (SPSS) version 22. Quantitative variables including age, haemoglobin was described as mean ± Standard Deviation, while qualitative variables including gender, haemoglobinopathies and their spectrum were described using frequencies and percentages. Results: In this study the mean age of the patients was 18.18±13.92 years, 169 (48.84%) patients were male and 177(51.16%) females. The frequency of haemoglobinopathies was found in 76 (21.97%) patients. The most common spectrum of haemoglobinopathies was beta thalassemia trait found in 52 (68.42%) patients followed by Beta thalassemia major 6 (7.89%) and HbD Punjab trait 4(5.26%). Conclusion: This study concluded that the frequency of haemoglobinopathies was 21.97% and the most common spectrum of haemoglobinopathies was Beta thalassemia trait followed by Beta thalassemia major & HbD Punjab Trait in patients referred to Haematology, Pathology Department, Services Hospital Lahore for workup of anaemia.